Detection of a strain of soybean mosaic virus affecting tropical forage species of Centrosema - Morales, Francisco José; Niessen, AI; Castaño, M.; Calvert, Lee A. (Scientific Societies, 1990)
A filamentous virus about 715 nm long was isolated from a plant of the tropical forage legume Centrosema macrocarpum affected by mosaic. Ultrathin sections of symptomatic leaf tissue showed pinwheel inclusions in the cytoplasm of infected cells. The virus was transmitted by mechanical means, by aphids, and through seed. Purified virus preparations had an absorbance ratio (A 260/280) of 1.13, contained a single protein of relative molecular weight 32,500, and had a 9-kb nucleic acid species. The virus was serologically indistinguishable from soybean mosaic virus and was related to bean common mosaic and watermelon mosaic-2 viruses. Based on the results of serological and pathogenicity tests, we conclude that the potyvirus isolated from C. macrocarpum is a strain of soybean mosaic virus.